Data on investigation of metabolomics and ionomics of Humulus lupulus grown in IndiaMendeley Data - Tripti Singh; Ashwani Mathur (Data in Brief)
The article reports data on chemical profiling of aqueous, methanolic, and n-hexane extract of field cultivated male Humulus lupulus using liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS). Also, the elemental profiling of the soil was carried out using Inductively coupled plasma mass spectrometry (ICP-MS). The elemental analysis revealed the soil to be rich in iron, calcium, magnesium, sodium, and potassium while trace elements like copper, cobalt, zinc, and molybdenum comparatively were found to be in lesser amounts. The diverse catalogues of compounds, identified in plant extracts, belong to different phytocompound groups, including phenolics, flavonoids, fatty acids, and alcohol derivatives. The compounds, such as Trans-2-methyl-4-n-pentylthiane, 2-Azido-2,4,4,6,6,8,8-heptamethylnonane were identified (with a similarity score > 65) in n-hexane, while compounds like Arsenous acid, tris(trimethylsilyl) ester and (Tris(tert-butyldimethylsilyloxy) arsane were identified in methanolic extract. The aqueous extract revealed compounds such as 2-Amino-1,3,4-octadecanetriol and Safingol with the highest peak area run in positive mode while Oleanolic acid and Gingerol have the highest peak area run in negative mode. The suggestive association between soil elemental composition, abiotic factors and plant germplasm, on phytochemical profile is proposed.